2020
DOI: 10.1097/md.0000000000022143
|View full text |Cite
|
Sign up to set email alerts
|

Baseline SUVmax of 18F-FDG PET-CT indicates prognosis of extranodal natural killer/T-cell lymphoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
1
8
1
Order By: Relevance
“…However, the initial PET SUVmax was ≤7, and univariate analysis showed that this factor had a favorable impact on CR acquisition. This was consistent with the findings of other studies that poor prognostic factors were present when the initial PET SUVmax was high 18,19 . Patients with relapsed or refractory mantle cell lymphoma or follicular lymphoma have various treatment options.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the initial PET SUVmax was ≤7, and univariate analysis showed that this factor had a favorable impact on CR acquisition. This was consistent with the findings of other studies that poor prognostic factors were present when the initial PET SUVmax was high 18,19 . Patients with relapsed or refractory mantle cell lymphoma or follicular lymphoma have various treatment options.…”
Section: Discussionsupporting
confidence: 91%
“…This was consistent with the findings of other studies that poor prognostic factors were present when the initial PET SUVmax was high. 18,19 Patients with relapsed or refractory mantle cell lymphoma or follicular lymphoma have various treatment options. These results suggest that RIT treatment can be an effective treatment option for some patients with low PET SUVmax and difficult autologous stem cell transplantation because of their old age or comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated FDG uptake of spleen is reported to be resulted from the activation of T cells and macrophages stimulated by IFN-γ (38). In other disease, Xia et al retrospectively analyzed 141 patients with extranodal NK/T lymphoma and found that SUVmax-lesions ≥ 9.65 was associated with poor prognosis (39).…”
Section: Discussionmentioning
confidence: 99%
“…18 F-Fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) is widely used for the diagnosis of neoplastic diseases. It helps differentiate between benign and malignant lesions, determine the stage of cancers, and plan treatment methods [ 1 , 2 , 3 , 4 , 5 , 6 ]. It is used to diagnose ischemic, inflammatory, and degenerative diseases [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%